(untitled) (Journal of Comparative & International Higher Education, 2022)
This article examines the experiences of a group of Japanese study abroad students in response to the purposeful replication of a Japanese environment by the New Zealand-based institution where they studied. Data were collected from 12 students via interviews spread over approximately 20 months, and revealed that management provided specifically for the Japanese students, isolating them from other groups within the college in different ways, which is contrary to frequently cited study abroad objectives. Some initial resistance by participants gave way to acceptance, demonstrated through personal activities which propagated the institution’s Japaneseness and an appreciation of management’s efforts to provide them with a familiar living and studying environment. The study provides insight into a specific study abroad site unusual in the overtly placed limitations on processes of integration, and subsequent participant responses to that. In doing so, it contributes to the recognition of the diversity of ways in which study abroad may occur.